A study on indoor air quality of office building / Ahmad Izzat Nazmi Muhammad - Muhammad, Ahmad Izzat Nazmi (Faculty of Architecture, Planning and Surveying, 2014)
In modern day, people mostly adult living in indoor compare to outdoor due to working purposed. A result of a research from cdc.gov,2014 indicate that people spent about 90% of their time indoor. The research also indicate that the air inside a building is more polluted compare to outdoor air. The problems arise when these indoor air quality affect the health of the occupants health. Therefore, three office building was studied in this research. In this studies, only one factor of indoor air quality is being focused which is dust in the air. By using appropriate equipment which is Dust Trak Meter, the air in the selected office room of case study building will be tested. Other than that, an interview to the occupant of the room will be conducted to get more information about the IAQ in the selected room. Finally, the data collected will be analyzed. The finding from the study shows dust concentration in each case study room are appropriate condition whereby room with renovation works represent the highest dust concentration. Follow up by the old office room and lastly the new office room that has lowest dust concentration. Thus, proper conclusion and recommendation will be provided to overcome the indoor air quality problems in the future.